Factors influencing safety behaviour among officers in the royal Malay regiment - Muhammad Nizar, Zaaba (2023)
Malaysian Army (MA) military personnel from Malaysian Armed Forces (MAF) receive a substantial amount of information and instruction in various aspects of warfare and strategy. The general objective of this study is to identify the factors influencing Safety behaviour among Royal Malay Regiment (RMR) Officers. This study collected data randomly from 565 officers in Malaysia, ranging in rank from Major (Maj) to Captain (Capt) / Lieutenant (Lt) / 2nd Lieutenant (2nd Lt). The sample size for this study was estimated using Krejcie and Morgan (1970), therefore, the sample taken is 234. The researcher administered an online survey by distributing a questionnaire link to all officers and facilitated by 26 Adjutants from all the present 26 units of RMR. Therefore, a total of 179 respondents or 76.4 percent have answered the questionnaire and managed to be collected almost one months. The researcher analysed the collected data using the Statistical Package for Social Science (SPSS) version 26 and for analysis data, the researcher chooses to use descriptive statistics and inferential statistics. The mean score for safety behaviour among the RMR Officers is 3.74, interpreted as the level of safety behaviour among the RMR Officer’s presence as moderately high. According to Multiple Regression analysis, there is a significant and positive relationship between Safety communication and feedback, and safety behaviour (β = 0.505, t = 5.349, p < 0.000). Meanwhile, there is no significant relationship between management commitment (β = - 0.037, t = 0.377, p < 0.706), safety training (β = 0.027, t = 0.334, p < 0.739), safety leadership (β = -0.113, t = -1.266, p < 0.207) and safety behaviour. The study of RMR Officers' safety behaviors emphasizes the importance of safety communication and feedback, as the RMR officers receive support from management, and demonstrating vigilance towards potential safety behaviour.